Nuclear Magnetic Resonance Treatment Accelerates the Regeneration of Dorsal Root Ganglion Neurons in vitro - Mann, Anda; Steinecker-Frohnwieser, Bibiane; Naghilou, Aida; Millesi, Flavia; Supper, Paul; Semmler, Lorenz; Wolf, Sonja; Marinova, Lena; Weigl, Lukas; Weiss, Tamara; Radtke, Christine (Frontiers in Cellular Neuroscience, 2022)
Functional recovery from peripheral nerve injuries depends on a multitude of factors. Schwann cells (SCs) are key players in the regenerative process as they develop repair-specific functions to promote axon regrowth. However, chronically denervated SCs lose their repair phenotype, which is considered as a main reason for regeneration failure. Previous studies reported a modulatory effect of low nuclear magnetic resonance therapy (NMRT) on cell proliferation and gene expression. To provide first insight into a possible effect of NMRT on cells involved in peripheral nerve regeneration, this study investigated whether NMRT is able to influence the cellular behavior of primary SC and dorsal root ganglion (DRG) neuron cultures in vitro. The effect of NMRT on rat SCs was evaluated by comparing the morphology, purity, proliferation rate, and expression levels of (repair) SC associated genes between NMRT treated and untreated SC cultures. In addition, the influence of 1) NMRT and 2) medium obtained from NMRT treated SC cultures on rat DRG neuron regeneration was examined by analyzing neurite outgrowth and the neuronal differentiation status. Our results showed that NMRT stimulated the proliferation of SCs without changing their morphology, purity, or expression of (repair) SC associated markers. Furthermore, NMRT promoted DRG neuron regeneration shown by an increased cell survival, enhanced neurite network formation, and progressed neuronal differentiation status. Furthermore, the medium of NMRT treated SC cultures was sufficient to support DRG neuron survival and neurite outgrowth. These findings demonstrate a beneficial impact of NMRT on DRG neuron survival and neurite formation, which is primarily mediated via SC stimulation. Our data suggest that NMRT could be suitable as a non-invasive auxiliary treatment option for peripheral nerve injuries and encourage future studies that investigate the effect of NMRT in a physiological context.